Respuesta :

Answer:

a + b = 27

=> a = 27 - b

ab = 50

So, (27 - b) x b = 50

27b - b^2 = 50

b^2 - 27b + 50 = 0

Solving, b = 25, 2

Hence,

Case 1: b = 25, a = 2

Case 2, b = 2, a = 25

Answer:

2, 25

Step-by-step explanation:

Let the numbers be x and y :

  • x + y = 27
  • xy = 50

Rearrange the first equation so it is equal to one variable :

  • y = 27 - x

Substitute the value in the second equation :

  • x(27 - x) = 50
  • 27x - x² = 50
  • x² - 27x + 50 = 0
  • (x - 25)(x - 2) = 0
  • x = 2, 25